Meningkatkan Kreativitas Mahasiswa Melalui Pembuatan Kerajinan Tangan Dari Limbah Koran Bekas - Dewi Fatmasari; Retno Djohar Juliani; Varisa Munatasya; Dini Fitria R (Jurnal Pengabdian kepada Masyarakat STIE AKA Semarang, 2025)
Used newspapers are one type of waste commonly found in household and office environments. If not managed properly, this waste can increase the burden of environmental pollution. To address this issue, a creative and innovative approach is needed through recycling activities that can transform used newspapers into useful and economical products, such as baskets, photo frames, and various household accessories. In addition to contributing to waste management, this activity also has the potential to create environmentally friendly business opportunities. Thus, the development of recycling skills for used newspapers can empower the community to be more environmentally conscious and improve economic welfare sustainably.